Edukasi Masyarakat Lingkungan VIII Titi Kuning Dalam Mendampingi Anak Belajar Daring - Diny Atrizka; Ikbar Pratama; Khalik Pratama; Agung Suharyanto (Universitas Medan Area, 2022)
The Covid-19 pandemic has occurred all over the world, including Indonesia. The corona virus-19 pandemic has changed human systems and behavior, as well as a new normal in the education system in Indonesia. In the education sector, there is a shift from getting an education at school to attending school from home through online or online learning methods. Studying from home is a challenge for parents of students who usually send their children to take lessons at school. The role of parents of children who study online is very important. Parents are expected and encouraged to play an active role in assisting and accompanying their children to learn and guiding their children to study at home, therefore as a public servant help make this online learning successfully by carrying out educational outreach education to the residents of the Community VIII Kelurahan Titi Kuning. The results of this service increase the knowledge and understanding of parents about online learning and increase awareness of the importance of accompanying children to learn online. The conclusion obtained from education campaigns for the importance of parents assisting children in online learning to increase public awareness of the Titi Kuning VIII Environment, especially parents of children who attend online learning methods at home play a big role in the success of children's learning.